Pengaruh Promosi Melalui Media Sosial Terhadap Pengambilan Keputusan Kursus Bahasa Inggris Pare Dengan Viral Marketing Sebagai Variabel Intervening - Ahmad Farih; Ahmad Jauhari; Eko Widodo (JMK (Jurnal Manajemen dan Kewirausahaan), 2019)
This study aims to determine the effect of promotion through social media on the decision of English language courses at CELL institutions Pare Kediri East Java - English Village with viral marketing as an intervening variable. The population in this study were course participants at the CELL institution Pare Kediri East Java - English Village. The sampling technique uses non-probability sampling technique which is accidental sampling and the number of samples is 100 respondents. This research is quantitative research. Data analysis is used using path analysis (path analysis) with the SPSS version 20.0 application. For the endogenous variable (Y) of this study is the purchase decision, for exogenous variables (X) is promotion through social media, and for intervening variables (Z) is viral marketing. The results of this study indicate that: (1) There is a positive significant influence between promotion through social media on purchasing decisions. (2) There is a positive significant influence between promotion through social media on viral marketing. (3) There is a significant positive influence between viral marketing on purchasing decisions. (4) Yes significant influence between promotion through social media on purchasing decisions with viral marketing as an intervening variable.